1995
DOI: 10.1287/orsc.6.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Crossroads Understanding Language Games

Abstract: In this essay, Mauws and Phillips argue that the current usage of the language game concept has been a very weak version. They assert that, as originally presented by Wittgenstein, it is a considerably more nuanced and powerful idea than has been previously presented in the organizational literature. They draw from Wittgenstein, from arguments outlined in the 1992 debate in Organization Science and from their own perspective on the meaning of language games to present a thoughtful, scholarly and very lucid tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 31 publications
1
54
0
2
Order By: Relevance
“…From this standpoint, comments on the efficiency of the standard often resemble a language game. The role of language games in the construction and dissemination of management tools has been highlighted in a number of studies most critical of managerial innovation (Astley and Zammuto, 1992;Mauws and Phillips, 1995;Zbaracki, 1998). More particularly, these studies showed that the new management models are often based on rhetoric of legitimization whose meaning is socially constructed and dissociated from organizational practices or performance.…”
Section: The Legitimacy-based Model: a Managerial Fashion To Conform mentioning
confidence: 99%
“…From this standpoint, comments on the efficiency of the standard often resemble a language game. The role of language games in the construction and dissemination of management tools has been highlighted in a number of studies most critical of managerial innovation (Astley and Zammuto, 1992;Mauws and Phillips, 1995;Zbaracki, 1998). More particularly, these studies showed that the new management models are often based on rhetoric of legitimization whose meaning is socially constructed and dissociated from organizational practices or performance.…”
Section: The Legitimacy-based Model: a Managerial Fashion To Conform mentioning
confidence: 99%
“…Mauws and Phillips 1995;Kieser 2002). Although both systems may operate within the economic system they develop different 'languages' and different criteria of success that cannot be translated into each other.…”
Section: The Multitude Of Autonomous Strategy Discoursesmentioning
confidence: 99%
“…The influence of scholars such as Wittgenstein, Foucault, and Derrida have now found their way into the most prestigious journals (e.g., Mauws & Phillips, 1995;Townley, 1993;Kilduff, 1993), and the basic ideas that they promoted are taken for granted by many organizational scholars. Linguistic approaches to organizations focus attention on the socially constructed and processual nature of organizations, and on the actual processes through which organizations are produced, maintained, and sometimes disassembled.…”
Section: Academy Of Management Annals Organizational Discoursementioning
confidence: 99%